Biologically conformal treatment: biomarkers and functional imaging in radiation oncology. (October 2008) - Lawrence, Yaacov Richard; Werner-Wasik, Maria; Dicker, Adam P
''Conformal radiation therapy'' is the standard of care in radiation oncology, referring to the process of shaping the radiation beam to precisely match a tumor''s physical dimensions. We describe ''biologically conformal radiotherapy'', in which the radiation oncologist matches the prescribed treatment to a tumor''s biological characteristics and the host''s predicted tolerance of radiation. This paradigm emphasizes that not all tumors are equally sensitive to radiation; conversely, some patients are especially susceptible to radiation''s side effects. Patients bearing radioresistant tumors or those prone to toxicity may be best treated with the incorporation of targeted radiation modulators or, in extreme cases, by a different modality. The biological characteristics of tumors can be assessed by a wide range of techniques: functional imaging (positron emission tomography and advanced magnetic resonance imaging), single gene/protein molecular techniques and ''omic'' technologies. This paper reviews the latest advances in the use of biomarkers and functional imaging in guiding patients to receive the most appropriate treatment.